“Currents of Hope”: Neurostimulation Techniques in U.S. and U.K. Print Media - Racine, Eric (Cambridge quarterly of healthcare ethics, 2007)
The application of neurostimulation techniques such as deep brain stimulation (DBS)—often called a brain pacemaker for neurological conditions like Parkinson's disease (PD)—has generated “currents of hope.” Building on this hope, there is significant interest in applying neurostimulation to psychiatric disorders such as major depression and obsessive-compulsive disorder (OCD). These emerging neurosurgical practices raise a number of important ethical and social questions in matters of resource allocation, informed consent for vulnerable populations, and commercialization of research.The authors acknowledge the help of Dr. Jarrett Rosenberg, Ofek Bar-Ilan, Stacey Kallem, Allyson Mackey, and Cynthia Forlini. This study was supported by the Institut de recherches cliniques de Montréal (E.R.), SSHRC (E.R.), and NIH/NINDS R01 #NS045831 (J.I.)